Design, modeling, and control of a dual-axis solar tracker using fractional order PID controllers for enhanced energy efficiency - Hayder Abdulsahib Issa; Layth Mohammed Abdali; Haider Alhusseini; Vladimir I. Velkin (Results in Engineering)
Dual-axis solar tracking systems play a critical role in maximizing photovoltaic (PV) energy yield by continuously aligning the solar panel orientation with the sun’s position throughout the day. However, these systems pose significant control challenges due to nonlinear dynamics, environmental disturbances, and the need for high-precision tracking. This paper presents the design, modeling, and performance evaluation of two dual-axis sun tracking controllers: a conventional proportional–integral–derivative (PID) controller and a fractional-order PID (FOPID) controller. While the FOPID controller introduces added complexity due to its five tuning parameters, it offers enhanced flexibility and potential for improved dynamic performance. The study aims to compare the two controllers in terms of tracking accuracy, response time, and overall energy harvesting efficiency. A system comprising a 340 W PV module, DC motors, a DC-DC boost converter, and a PWM driver is modeled and simulated. Results demonstrate that the FOPID controller achieves superior performance with faster response, reduced oscillations, and improved sun-tracking precision. Comparative analysis indicates that the use of FOPID control enhances energy harvesting by approximately 8–12 %. These findings underscore the potential of advanced fractional-order control in enhancing the performance of solar tracking systems and contribute to the broader development of efficient renewable energy technologies.